Shear Bond Strength of Ceramic Veneers to Zirconia–Calcium Silicate Cores - Ting-Yi Chiang (MDPI AG, 2021)
Improving the bond strength of veneering ceramics to ZrO2-based cores remains a challenge. The purpose of this study was to evaluate the shear bond strength of different ZrO2 cores containing calcium silicate (CaSi) to veneering ceramics. Five types of ZrO2-based cores (n = 230) were divided into two groups: with or without oxygen plasma treatment. These were bound to two veneering ceramics (IPS e.max Ceram or VITA VM9). Shear bond strength of veneering ceramics to various cores was measured (n = 10), in addition to phase composition, surface morphology and contact angle of the cores. The results indicated that the plasma treatment had a significant effect on the water contact angle of the ZrO2-based cores, but had little effect on the bond strength. Regardless of plasma treatment, the highest strength value was recorded in the ZrO2 core specimen containing 20 wt % CaSi, when all cores were adhered to VITA VM 9 veneer. When using IPS e.max Ceram veneer, the shear bond strength of the plasma-treated 20 wt % CaSi-containing ZrO2 core was 16.6 ± 0.9 MPa higher than that of VITA In-Ceram YZ core control (13.4 ± 1.0 MPa) (p < 0.05). We conclude that the presence of 20 wt % CaSi in ZrO2 can improve the shear bond strength of zirconia-based cores to veneering ceramic.